Comparison of the diagnostic accuracy of diffusion-weighted and dynamic contrast-enhanced MRI with 18F-FDG PET/CT to differentiate osteomyelitis from Charcot neuro-osteoarthropathy in diabetic foot. Issue 132 (November 2020) - Diez, Ana I. Garcia; Fuster, David; Morata, Laura; Torres, Ferran; Garcia, Ruben; Poggio, Daniel; Sotes, Santiago; Del Amo, Montserrat; Isern-Kebschull, Jaime; Pomes, Jaume; Soriano, Alex; Brugnara, Laura; et al.
Highlights: Functional MR parameters are useful for differentiation between DFO and CN. Functional MR measurements with large ROIs provide more reliable results. 18 F-FDG PET/CT showed greater diagnostic performance than functional MRI. 18 F-FDG PET/CT is a good imaging tool when nuclear medicine studies are required. Abstract: Purpose: To compare the diagnostic accuracy of diffusion-weighted imaging (DWI) and dynamic contrast-enhanced-magnetic resonance imaging (DCE-MRI) involving two region of interest (ROI) sizes with 18-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) to differentiate diabetic foot osteomyelitis (DFO) from Charcot neuro-osteoarthropathy (CN). Method: Thirty-one diabetic patients were included in this prospective study. Two readers independently evaluated DWI (apparent diffusion coefficient [ADC] and high-b-value signal pathological-to-normal bone ratio [DWIr]) and DCE-MRI parameters ( K trans, Kep, Ve, internal area under the gadolinium curve at 60 s [iAUC60 ] and time intensity curve [TIC]) using two different ROI sizes, and 18 F-FDG PET/CT parameters (visual assessment, SUVmax, delayed SUVmax, and percentage changes between SUVmax and delayed SUVmax ). Techniques were compared by univariate analysis using the area under the receiver operating characteristic curve [AUC]. Reliability was analyzed with Kappa and Intraclass correlation [ICC]. Results: DWIr, K trans and iAUC60 showed better diagnostic accuracy (AUC = 0.814−0.830) and reliability (ICC > 0.9) for large than for small ROIs (AUC = 0.736−0.750; ICC = 0.6 in K trans, 0.8 in DWIr and iAUC60 ). TIC showed moderate diagnostic performance (AUC = 0.739−0.761) and reliability (κ 0.7). Visual assessment of 18 F-FDG PET/CT demonstrated a significantly higher accuracy (AUC = 0.924) than MRI parameters. Semi-quantitative 18 F-FDG PET/CT parameters did not provide significant improvement over visual analysis (AUC = 0.848−0.903). Conclusion: DWIr, K trans and iAUC60 allowed reliable differentiation of DFO and CN, particularly for large ROIs. Visual assessment of 18 F-FDG PET/CT was the most accurate technique for differentiation.